Pengaruh Motivasi Kerja Dan Lingkungan Kerja Terhadap Kinerja Pegawai Pada Kantor Camat Talang Kelapa Kabupaten Banyuasin - Inda Zarkasi; Hamid Halin; Luis Marnisah (Jurnal Bisnis, Manajemen, dan Ekonomi, 2022)
This study aims to analyze the influence of motivation and work environment on employees’ performance at the talang kelapa District Office, Banyuasin Regency. Data were collected through observation and quistionnaires. This study implemented the multiple linear regresseion method to analyze data. The result of the investigation unveil that partially the work motivation has a significant effect on employees performance. Simultaneously, otivation and work environment have a significant effect on employees’ performance. These empirical findings can provide benefits for the Talang Kelapa District Office in Banyuasin Regency. The leaders of this government institusion should pay attention to motivational and work environment factors to improve employee performance